APPLICATION OF BIOTHECHNOLOGY AGRICULTURAL BY MANURE, EFFORT OF SESAME PRODUCTION IN COASTAL SANDY LAND - Taryono & Eko Hannudin, Dewi Ratna Nurhayati, Yudhono, Prapto, (Proceeding of International Congress, 2014)
Coastal sandy land as one of marginal land which potential become to be a sustainable productiveland. Annual crops such as Sesame cultivation proper to developed as an agribusiness crops in coastalsandy land. Integrated fertilizer model ( by manure, or organic fertilizer and in organic fertilizer )Manurefertilizer, is one of Biotechnology in agricultures products. This study aimed to know the growth andyield of Sesame (Sesamum indicum L.) in quantity and quality through the combination treatment of manureand inorganic proportionately which refers to the dose and type of manure elected. Phase II studyconducted in a polybag, for planting. This study conducted in Banguntapan Yogyakarta, Agricultural stationlab. from September â December 2012 aimed to determine the proportion of fertilizer best combinationof sesame results based on the dose of manure was selected from the results of the Phase I study(chicken manure 30 t / ha).This study used a factorial experiment (7 X 2) were prepared by completely randomized design (CRD)with repetition three times. Experiment arranged in factorial with twoâfactor, repeated three times. Firstfactor is combination of manure and inorganic fertilizer (K), there are 7 types: (Sandy Land media: K0 1.Chicken manure 30 t / ha: K1, 2. Chicken manure 15 tonnes / ha (100% recommendation farmers) + inorganicfertilizers (N, P, K deficiency is equivalent to substitute 15 tonnes / ha of chicken manure): K2, 3.chicken manure 11.25 tonnes / ha (75% of farmers recommendation) + inorganic fertilizers (N, P, K deficiencyreplacement dose equivalent to 18.75 tonnes / ha of cow manure): K3 4. chicken manure 7.5 t / ha(50% of farmers recommendation) + inorganic fertilizers (N, P, K deficiency replacement dose equivalentto 22.5 tonnes / ha of chicken manure): K4 ,5. chicken manure 3.75 t / ha (25% of farmers recommendation)+ inorganic fertilizers (N, P, K deficiency replacement dose equivalent to 26.25 tonnes / ha of chickenmanure): K5 ,6. inorganic fertilizers (N, P, K deficiency replacement dose is equivalent to 30 tons / ha ofchicken manure): K6.Second factor is the variety: Sumberrejoâ1, Sumberrejoâ2, Variable observed were:plant height, days to flowering, day of harvest, seed weight per plant, weight of 1000 seeds, and seed oilcontent. The data analyzed by Anova 5%, with further testing Duncan 5%. The results showed The fastestflowering (45 days) was on the control treatment. The age of harvest is almost the same, 105 days. Highesttotal seed oil content, 42.72%, obtained in the treatment of chicken manure 7.5 t / ha (50% of farmers recommendation)+ inorganic fertilizers (N, P, K deficiency replacement dose equivalent to 22.5 tonnes / haof chicken manure) in Sumberrejoâ1Keywords: Coastal sandy land, organic fertilizer, in organic, Sumberrejoâ1, Sumberrejoâ2 Sesame(Sesamum indicum L.)